Chitosan nanoparticles as potential antimicrobial coating - Peršin Fratnik Zdenka; Maver, Uroš; Kolar, Metod; Šauperl, Olivera; Fras Zemljič Lidija; Vihar, Boštjan (Acta Medico-Biotechnica, 2024)
Purpose: To evaluate the antimicrobial efficacy of chitosan nanoparticles in comparison to a chitosan solution, as well as to assess their practical application on medical textile materials. Methods: Dispersions of nanoparticles with different weight fractions of chitosan were prepared. An optimal chitosan nanoparticle system for textile material application was identified based on analyses of charge, particle size, changes in surface charge (zeta potential), concentration of free amine groups (polyelectrolyte titration), morphology, and antimicrobial properties. The effect of the nanoparticles dispersion application compared to the chitosan solution was determined using the ASTM E2149-01 antimicrobial test with Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria and a fungus (Candida albicans). Results: More effective application of chitosan was noted with the incorporation of chitosan nanoparticles. Applying chitosan on the inside and outside of the functional material enhanced the specific surface area and improved the accessibility of the chitosan coatings. Applying chitosan nanoparticles provided effective antimicrobial protection against all three microorganisms tested. Conclusions: Chitosan deposition in the form of nanoparticles compared in form of solution, offered better antimicrobial protection. Such functionalised material presents a promising application in medical textile materials.